Pengaruh Disiplin Kerja Rekonsiliasi Satuan Kerja Dalam Aplikasi E–Rekon–LK Terhadap Kinerja Pegawai Bagian Seksi Verifikasi Dan Akuntansi Pada Kantor Pelayanan Perbendaharaan Negara Buntok Tahun 2020: The Effect of Working Unit Reconciliation Discipline in E-Recon-Lk Application on Employee Performance in Verification and Accounting Section in Buntok State Budget Services Office 2020 - Lisawanto, Lisawanto (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2020)
This study aims to determine and describe the effect of Work Unit Reconciliation Work Discipline on the e-Rekon-LK Application on Employee Performance in the Verification and Accounting Section at the Buntok State Treasury Service Office in 2020 and to find out and describe the most influential indicators on work discipline unit reconciliation. work (Satker) in the e-Rekon-LK application on the performance of employees of the verification and accounting section. The theory used in this research is Work Discipline according to Bejo Siswanto (2019: 291) and employee performance theory according to Agus Dwiyanto (2017: 47). This research uses descriptive quantitative method with data collection techniques using observation, interviews, documentation and questionnaires. This study has two variables, namely the independent variable (X) work unit reconciliation discipline in the e-rekon-lk application and the dependent variable (Y) the employee performance in the verification and accounting section. The data analysis tool used is Simple Linear Regression using SPSS Version 25. The hypothesis in this study is H1. It is suspected that there is an influence between the work unit reconciliation work discipline (satker) in the e-Rekon-LK application on the performance of employees of the verification and accounting section of the Buntok State Treasury Service Office 2020, H2. It is suspected that the level of vigilance in the work unit (Satker) reconciliation work discipline indicator in the e-Rekon-LK application has the most influence on employee performance in the verification and accounting section. The results obtained in the calculation of simple linear regression are Y = 10.946 + 0.765 X where the value (a) is 10.946 and the coefficient value (b) is 0.765. Then the tcount is obtained from the above test that tcount> ttable (5.876> 2.035) then Ho is rejected and Ha is accepted, meaning that there is a significant influence between Work Discipline Work Unit Reconciliation (Satker) in the e-Rekon-LK Application on the Performance of Section Employees Verification and Accounting Section at the Buntok State Treasury Service Office 2020.